Financial adjustment for the trend of financial policy of the Iraqi cooperative agricultural bank – during the period (1992-2015). - عبد الرحيم, ثريا; عذافة, حيدر حسين (Journal of Economics and Administrative Sciences, 2019)
AbstractFinancing is one of the important pillars for activating and activating the agricultural sector, through which we can see an agricultural project on the ground. However, supplying the agricultural sector with financial resources requires a credit policy that is capable of making the right financing decision, because the financial resources are limited. The credit policy, and the financing decision, must be the best use not only to provide the necessary money, but to work to provide everything that would develop and activate the agricultural sector.The transformation of the Agricultural Cooperative Bank of Iraq from specialized banking to the overall would lead to a decrease in the volume of interest in the agricultural sector, which is the main reason for the establishment of a bank, its function to provide everything related to support and support for agricultural projects.